Quality Management, Green Innovation and Firm Value: Evidence from Indonesia - Husnaini, Wahidatul; Tjahjadi, Bambang (International Journal of Energy Economics and Policy, 2020)
The purpose of this study is to examine the effect of quality management on green innovation, as measured by green process innovation and green product innovation. The study also aims to examine the effect of green innovation as a mediating variable between quality management and firm value. Data were collected from 352 annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the financial year 2014-2017. The study employed simple regression analysis, multiple regression and Sobel Test for hypotheses testing. The results showed that quality management has a positive effect on green process innovation, but not with green product innovation. Quality management decreases firm value, but, when the company conducts a green process innovation together with quality management, firm value increases. Being an ISO 9001 certified company does not guarantee implementing green product innovation because it requires a large investment. Companies can enhance firm value by simultaneously and consistently employing quality management, green process innovation and green product innovation. Keywords: quality management; green process innovation; green product innovation; firm value JEL Classifications: Q56, G32 DOI: https://doi.org/10.32479/ijeep.10282